2022
DOI: 10.3390/su14106058
|View full text |Cite
|
Sign up to set email alerts
|

Increasing the Livability of Open Public Spaces during Nighttime: The Importance of Lighting in Waterfront Areas

Abstract: The contemporary way of life influences the forms and time framework of outdoor activities in open public spaces, shifting their focus to nighttime usage. The aim of this study is to demonstrate the limits of existing outdoor lighting design standards and recommendations in terms of livability. As an exploratory case study, the Sava waterfront in New Belgrade, Serbia was chosen. The methodology consisted of theoretical research and specific analysis, which included: (1) mapping the spatial distribution of user… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
16
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(18 citation statements)
references
References 71 publications
(126 reference statements)
1
16
0
1
Order By: Relevance
“…This finding corresponds with other recent studies [10]. It contradicts most of the research on perceived safety, concluding that uniformed urban areas with white-coloured lighting appear to be the safest [44], [45]. Although non-uniformity was only one of the findings from the field study, the need for visible surroundings was also an important theme.…”
Section: Discussionsupporting
confidence: 64%
“…This finding corresponds with other recent studies [10]. It contradicts most of the research on perceived safety, concluding that uniformed urban areas with white-coloured lighting appear to be the safest [44], [45]. Although non-uniformity was only one of the findings from the field study, the need for visible surroundings was also an important theme.…”
Section: Discussionsupporting
confidence: 64%
“…As indicated in Appendix A, most studies (25)—all conducted since 2012—referred to LED lights (e.g., Haans & de Kort, 2012; Markvica et al, 2019; Nikunen et al, 2014; nine addressed HPS lamps (e.g., Boyce et al, 2000; Peña-García et al, 2015; Rea et al, 2009); and eight studies—most of them performed during the 2000s—addressed MH sources (e.g., Boyce et al, 2000; S. A. Fotios & Cheal, 2007; Hamsa et al, 2009; Rakonjac et al, 2022). In additional, latest smart-technologies may change place perception by introducing variable light- and temporal distribution, for example by dimming according to pedestrians’ locations or by the time of night.…”
Section: Resultsmentioning
confidence: 99%
“…Regarding age, Knight (2010), Johansson et al (2011), and Rahm and Johansson (2021) found no correlation with perceived safety. As to the influence of gender, the reviewed studies show inconsistent results, where Knight (2010) reported no influence on perceived safety, Haans and de Kort (2012) discovered that perceived safety depends on the perception of attractiveness-to-criminal activity rather than on gender; Rakonjac et al (2022) found that young women felt safer and more comfortable than men, and Loewen et al (1993) found that women tend to fear dark more than men.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations